Inuvialuit Living Art: Co-Creating Local Community Archaeology and Cultural Heritage Research - Lau, Jason YF (Scholarship@Western, 2022)
This thesis explores Inuvialuit cultural heritage through the lens of Inuvialuit Pitqusiat Inuusimitkun or living art, a term coined by Iñupiaq/Inuvialuk Elder Pauline Saturgina Tardiff and translated to Sallirmiutun by Inuvialuit Elders Albert and Shirley Elias. Using semi-structured interviews, focus groups, and ethnography, it brings together the knowledge of 11 Inuvialuit artists to discuss Inuvialuit living art through: its ability to tell stories through time and space; its role in surviving and thriving on the land; and its connection to inner “heartwork”. Using a community-based participatory research (CBPR) framework, it outlines the 2019 Inuvialuit Living History Culture Camp at Ivvavik National Park, where living art, photovoice, and participatory design were employed in action with nine Inuvialuit research partners to co-create visual products and documentation of Inuvialuit cultural heritage. This thesis concludes that living art is a vital aspect of Inuvialuit cultural heritage and advocates for continued engagements with living art, musicality, and a heart-centred approach in the future of archaeological research.